Coming back to jail: women, trauma, and criminalization - Comack, Elizabeth (Fernwood Publishing, 2018)
"Published some two decades ago, Elizabeth Comack's Women in Trouble explored the connections between the women's abuse histories and their law violations as well as their experience of imprisonment in an aged facility. What has changed for incarcerated women in those twenty years? Are experiences of abuse continuing to have an impact on the lives of criminalized women? How do women find the experience of imprisonment in a new facility? Drawing on the stories of forty-two incarcerated women, Coming Back to Jail broadens the focus to examine the role of trauma in the women's lives. Resisting the popular move to understand trauma in psychiatric terms--as post-traumatic stress disorder (PTSD)--the book frames trauma as "lived experience" and locates the women's lives within the context of a settler-colonial, capitalist, patriarchal society. Doing so enables a better appreciation of the social conditions that produce trauma and the problems, conflicts and dilemmas that bring women into the criminal justice net. In Coming Back to Jail, Comack shows how--despite recent moves to be more "gender responsive"--the prisoning of women is ultimately more punishing than empowering. What is more, because the sources of the women's trauma reside in the systemic processes that have contoured their lives and their communities, true healing will require changing women's social circumstances on the outside so they no longer keep coming back to jail."--